Determinasi Pemberian Kredit terhadap Kualitas Kredit di PT Pegadaian (PERSERO) Cabang Singaraja - Kadek Yoga Ari Putra; Ni Wayan Yulianita Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The purpose of this study was to determine the effect of the control environment, risk assessment, control activities, information and communication, monitoring, on bad loans at PT. Pegadaian (PERSERO) Singaraja Branch. This study uses a quantitative research design using a data collection instrument in the form of a questionnaire. The population that is the object of research is all employees of PT Pegadaian (Persero) Singaraja Branch which includes nine pawnshops and one pawnshop branch office. Determination of the sample using purposive sampling method with respondents' criteria, namely the head of the branch or head of the unit, credit analyst, and collateral estimator. So that the number of respondents obtained is 32 employees and 4 employees who do not meet the criteria because they are outside of the three predetermined criteria. Data analysis in this study used quantitative methods using SPSS version 16. The results showed that the variables of the control environment, risk assessment, control activities, information and communication, and monitoring had a negative and significant effect on bad loans.